Pleurotus spp: A cosmopolitan fungi of biotechnological importance (Scientia Agropecuaria, 2025)
The genus Pleurotus presents a multivariate species diversity due to its ability to grow in different substrates and environments. Whether wild or cultivated, they are edible mushrooms, as they present a high nutritional value and are medicinal due to their bioactive compounds with positive health effects. The aim of this review is to highlight the importance of the genus Pleurotus, since it is a cosmopolitan mushroom, and its properties can be used in different industrial applications and be a functional alternative for our future. Due to their saprophytic nature, they produce enzymes that act on the substrate in which they grow, degrading lignocellulosic material such as wood, forest and agricultural residues, hardwoods, wood by-products, cereal straw, bagasse, etc., and thanks to this degradative capacity, their enzymes are used in a wide range of biotechnological and environmental applications. In order to increase their production and consumption not only for their nutritional qualities, but also for their nutraceutical and biotechnological qualities, ease of cultivation, low investment cost, etc., new ways are being sought to increase their performance in cultivation. Recently, research has expanded the search for alternative uses of the Pleurotus genus, which has led to an increase in its cultivation, as well as its application in different fields of biotechnology. The cultivation of Pleurotus mushrooms represents an opportunity to generate a sustainable process and incorporate the process into a circular economy, generating environmental, social and economic benefits. The use of agro-industrial substrates and the subsequent reuse of the spent substrate as compost or organic fertilizer reduces the amount of waste that ends up in landfills and minimizes methane production. This allows for a more sustainable and environmentally friendly production model. Therefore, it is necessary to develop strategies for the promotion, marketing and sustainable production of products derived from these fungi.
Keywords: functional food; biodegradation; bioremediation; bioactive compounds; nutraceutical; Pleurotus